(untitled) (Zamonaviy ilmiy-texnik tadqiqotlar, 2025)
In the process of teaching mathematics in vocational schools, one of the most important tasks is to study the conditions of interdisciplinary integration and with the help of professional-oriented tasks. But in the process of doing this, the establishment of interdisciplinary ties in the sequence of professional-oriented issues in the education of vocational schools, the content of educational material today is considered one of the main tasks. For this reason, this article cites systematic directions in the formation of professional competencies as tasks for its implementation, and it is about the methods, tasks, functions, directions of training students of vocational schools and its results.